2019
DOI: 10.1038/s42003-019-0710-1
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive dominance can decrease behavioral complexity on subordinates through synchronization of locomotor activities

Abstract: Social environments are known to influence behavior. Moreover, within small social groups, dominant/subordinate relationships frequently emerge. Dominants can display aggressive behaviors towards subordinates and sustain priority access to resources. Herein, Japanese quail (Coturnix japonica) were used, given that they establish hierarchies through frequent aggressive interactions. We apply a combination of different mathematical tools to provide a precise quantification of the effect of social environments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Other studies show that dominant birds and their subordinates showed a high level of synchronization in the locomotor pattern. These findings suggest that dominance can potentially modulate behavioral dynamics through the synchronization of locomotor activities (ALCALA et al 2019).…”
Section: Behavior Of Domestic Chickensmentioning
confidence: 85%
“…Other studies show that dominant birds and their subordinates showed a high level of synchronization in the locomotor pattern. These findings suggest that dominance can potentially modulate behavioral dynamics through the synchronization of locomotor activities (ALCALA et al 2019).…”
Section: Behavior Of Domestic Chickensmentioning
confidence: 85%
“…Advanced signal processing analysis of experimentally obtained time series from self-synchronized Saccharomyces cerevisiae (yeast) cell cultures 23 , mammal cardiac cells 24,25 , quail locomotion 26 and mice wheel running 27 have shown multi-oscillatory, dynamically functional patterns of behavior. These dynamic patterns hold over a broad range of temporal scales for at least 3 orders of magnitude: 13 h -4 min in yeast (dissolved O2 and CO2) 23,28 , 100 s-220 ms in cardiac muscle cells (mitochondrial membrane potential and NAD(P)H) 24,28 , 24 h -15min in quails locomotion 18,26,27,29 .…”
Section: Introductionmentioning
confidence: 97%
“…Existing knowledge shows that both the liver clock and feeding rhythms are required for temporal coordination and alignment of physiology and metabolism with geophysical time 12 . It is difficult to overstate the importance of these questions, since rhythmic misalignment is linked to aging and disease [13][14][15][16] as well as their mechanistic underpinnings with physiology, metabolism 17 and behavior 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to gain insight into the temporal dynamics of behavior by rethinking the de nition of behavioral events. Using datasets of behavioral time series of Japanese quail (Coturnix japonica) within social groups 19,20 we explore the effect of the sampling interval used and how behavior is de ned (coarse-or ne-grained) on the distribution of events. We assessed not only Probability Distributions (PD), which provide information regarding how likely is an event of a given duration to occur, but also Relative Distribution (RD).…”
Section: Introductionmentioning
confidence: 99%